Religion and secularity : transformations and transfers of religious discourses in Europe and Asia - Eggert, Marion (Dynamics in the history of religion, 2013)
Religion and Secularity assembles studies on the concept of "secularity" in various cultures, thereby tracing the entangled history of the modern re-configuration of the religious field across the Eurasion continent